2008
DOI: 10.3141/2051-09
|View full text |Cite
|
Sign up to set email alerts
|

Using Warm-Mix Asphalt Technology to Incorporate High Percentage of Reclaimed Asphalt Pavement Material in Asphalt Mixtures

Abstract: The use of reclaimed asphalt pavement (RAP) helps save natural resources and money. The percentage of RAP that can be utilized successfully in hot-mix recycling is primarily dictated by practical considerations. To avoid deterioration of the aged binder, RAP should not be exposed to relatively high temperatures. This study investigated the feasibility of using a warm-mix asphalt (WMA) additive, Sasobit H8, in successfully recycling hot-mix asphalt (HMA) with 75% RAP at a lower temperature. A control HMA was pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
38
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(46 citation statements)
references
References 3 publications
2
38
0
3
Order By: Relevance
“…The addition of Sasobit could increase the high temperature grading of the asphalt binder [46]. Latter, Mallick et al (2008) have investigated the feasibility of using a WMA additive, Sasobit, with 75% reclaimed asphalt pavement (RAP) for producing a base course at a lower temperature and found that the performance of WMA with RAP was dependent on the stiffness of the combined (rejuvenated) binder in the mixture [47]. Moreover, have investigated the performance properties of WMA binders (Aspha-Min and Sasobit) containing aged binder.…”
Section: A Case Studiesmentioning
confidence: 99%
“…The addition of Sasobit could increase the high temperature grading of the asphalt binder [46]. Latter, Mallick et al (2008) have investigated the feasibility of using a WMA additive, Sasobit, with 75% reclaimed asphalt pavement (RAP) for producing a base course at a lower temperature and found that the performance of WMA with RAP was dependent on the stiffness of the combined (rejuvenated) binder in the mixture [47]. Moreover, have investigated the performance properties of WMA binders (Aspha-Min and Sasobit) containing aged binder.…”
Section: A Case Studiesmentioning
confidence: 99%
“…As a result of this, aggregates are completely coated with the binder at a lower temperature than required for HMA. RAP-WMA mixes utilize lesser virgin material and result in reduced CO 2 emissions and this makes it environment friendly [4,11]. WMA mixes prepared with RAP show similar properties to conventional HMA mixes [12].…”
Section: Introductionmentioning
confidence: 99%
“…As raw material and petroleum extraction involves huge cost, lot of study is being conducted across the globe to search for new materials which are durable and show good performance at low cost [3]. Using RAP to produce cold or hot mix asphalt is one of the methods which aims at cost reduction [4]. The re-use of aggregates and bitumen present in RAP aids in saving natural resources, money and is eco-friendly [5].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, RAP contents from 10% to 30% by mass of the mixture are considered to be adequate to produce asphalt mixtures with performance similar to conventional mixtures [4][5][6]. Rejuvenators, additives and warm mix asphalt technology are usually employed to improve the effective contribution of RAP binder towards the total binder of the mixture [7][8][9]. However, the use of RAP is at a very low level in many developing countries, for there are no relevant and unified recycling guidelines.…”
Section: Introductionmentioning
confidence: 99%